A microwave integrated preparation method of a few-layer x% M using phosphate rock as raw material a P b / BP method, device and application
Through the microwave integrated method, the phosphorus ore is used as the raw material to prepare a small layer of X % MAPB/BP composite material, solving the problem of stability and large -scale production in existing technology, and achieved efficient and cheap composite materials preparation, which has improved, and improved. Scope of application.
Patent Information
- Application Number
- CN202410061795.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-01-16
AI Technical Summary
In the prior art, when preparing metal phosphide/black phosphorus composite materials, it is difficult to ensure stability and large-scale production, and the raw material cost is high.
The microwave integrated method uses phosphorus ore as the raw material, and the combination of the oxidation reaction and the combination of the gas membrane separator is used to prepare a small layer of X % MAPB/BP composite material to achieve integrated preparation of phosphorus ore -to -phosphorus products.
It has achieved efficient, stable, simple and cheap preparation of composite materials, with easy operation, low reaction temperature, good stability and repeatability, and low energy consumption. It can adjust product types according to needs and increase the scope of applications.
Smart Images

Figure BDA0004666792140000081 
Figure BDA0004666792140000091 
Figure HDA0004666792150000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, in particular to a method for preparing a nanostructured ... a P b / BP method, device and application. Background Art
[0002] Metal phosphide (MP) materials have a unique electronic structure similar to that of precious metals, and possess physical and chemical properties that are adjustable with changes in composition. As the advantages of different bonds such as metal-metal bonds, phosphorus-phosphorus bonds, or metal-phosphorus bonds are exposed, the adsorption, dissociation behavior, thermal stability, thermal conductivity, electrical conductivity and other properties of the material will change. Therefore, by regulating the composition and structure of metal phosphides, their physical and chemical properties can be effectively changed, thereby obtaining different catalytic activities.
[0003] Black phosphorus (BP) is a two-dimensional material with more comprehensive performance than graphene. Its narrow band gap and layered structure give it excellent physical properties. It is called the "dream material" of the 21st century and has gradually attracted widespread attention. It has a high hole mobility at room temperature, which makes up for the shortcomings of other materials in the application of photoelectrochemical devices. It also has a high absorption coefficient and photothermal conversion efficiency, good biodegradability and biocompatibility, and is an ideal biomedical carrier. It is also a flame retardant and preservative with good performance, and can achieve good flame retardant effect at extremely low addition amounts. The strong electron-donating property of black phosphorus makes it show good application prospects in photoelectrocatalysis.
[0004] In the composite material composed of metal phosphide (MP) / black phosphorus (BP), the bonding effect between the interfaces of different components can improve the electron transfer rate. The different chemical compositions and crystal structures in the composite material will cause lattice strains such as tension and compression, which will affect the adsorption energy of the site to the intermediate and improve the catalytic activity of the material. The different energy band arrangements of different phases will lead to charge transfer at the interface, which is beneficial to the surface electronic modulation of the composite material. In addition, in the multi-metal phosphide / black phosphorus composite material, there are abundant metal-metal bonds and metal-phosphorus bonds, which make it have better chemical stability and faster charge transfer rate than single metal phosphide / black phosphorus. At the same time, the chemical diversity of multi-metal ions can produce enough active sites on the surface of low-coordination bonds, so the synergistic effect of more components plays a vital role in improving its reaction efficiency or changing its selectivity.
[0005] Patent CN112607716A discloses a method for preparing nickel phosphide nanosheets and nickel phosphide nanosheets prepared by the method, the method comprising: mixing a nickel salt solution and a black phosphorus nanosheet dispersion by stirring to obtain a mixed dispersion; treating the mixed dispersion to obtain a nickel phosphide nanosheet dispersion; filtering and washing with anhydrous ethanol until no N-methylpyrrolidone remains, washing the filter cake with deionized water, and dispersing the filter cake in deionized water for freeze drying to obtain the final product, nickel phosphide nanosheets. This method uses a metal salt solution and black phosphorus as raw materials and is carried out in a solution. It is difficult to ensure that a few-layer nickel phosphide nanosheets are obtained stably, and black phosphorus is expensive and cannot be prepared on a large scale.
[0006] Patent CN116536699A discloses a black phosphorus-iron phosphide composite nanocatalyst, which is a nano binary composite structure formed by pebble-shaped iron phosphide nanocrystals being wrapped by black phosphorus crystals. Using a one-step synthesis process of ball milling, red phosphorus powder and iron powder are directly converted into nanoparticles with black phosphorus-iron phosphide composite components under appropriate process conditions, and the active sites distributed on the surface are further exposed after simple cleaning and dispersion. However, this method uses red phosphorus powder and iron powder as raw materials, requires organic solvent cleaning, has cumbersome steps, and the particle uniformity and low number of layers of the obtained black phosphorus-iron phosphide composite nanocatalyst are difficult to guarantee.
[0007] In summary, the preparation of metal phosphides using black phosphorus or red phosphorus, metal salts or metal powders as raw materials is not universal; the present invention uses phosphate rock as raw material, which not only has a wide source, but also can maximize the utilization of phosphorus, metal oxides and metal-like oxides therein. Therefore, it is necessary to provide an efficient, stable, simple and inexpensive integrated preparation method of a few-layer metal phosphide / black phosphorus composite material using phosphate rock as raw material to solve the above problems, and to adjust the gas separation membrane channel according to actual needs to separate different products such as pure black phosphorus, pure metal phosphide, and few-layer metal phosphide / black phosphorus composite materials. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention aims to provide a microwave integrated preparation method for preparing a small layer of x% M using phosphate rock as raw material. a P b The method, device and application of / BP, the method uses phosphate rock as raw material, adopts microwave integration method, according to the different metal oxide contents in phosphate rock and the current demand, chooses to add or not add additional metal oxides, directly prepares few-layer black phosphorus (BP), few-layer metal phosphide / black phosphorus composite materials (x% M a P b / BP) or few-layer metal phosphide (M a P b), has excellent energy storage, photoelectrocatalytic and other properties, and realizes the full utilization of phosphorus, metal oxides and metal-like oxides in phosphate ore.
[0009] In view of the problems that most of the current domestic phosphate rocks are of medium and low grade and have low utilization rate, the present invention uses phosphate rock as raw material to prepare a few-layer x% M a P b / BP, making full use of P2O5, SiO2 and metal oxides in phosphate ore, adding or not adding additional metal oxides, in an inert gas environment and under relatively low microwave irradiation power, redox reaction is carried out to promote the formation of metal-metal bonds, phosphorus-phosphorus bonds or metal-phosphorus bonds; adding mixed catalysts under high-intensity microwave irradiation power to promote the generation of metal phosphides and black phosphorus gas, and separating the inert gas, waste gas and gaseous x%M through a gas membrane separator a P b / BP separation, the inert gas is mixed with the original inert gas and continued to be used, and the gaseous x%M a P b / BP condensation collection can get x%M a P b / BP composite materials, including few-layer black phosphorus (BP), few-layer metal phosphide / black phosphorus composite materials (x% M a P b / BP) or few-layer metal phosphide (M a P b This method can realize the integrated preparation of phosphate ore to phosphorus-containing products, is easy to operate, has low reaction temperature, good stability and repeatability, low energy consumption, and can adjust the product type according to actual needs to obtain different minority layer x% M a P b / BP, thereby increasing its application range.
[0010] To achieve the above object, the present invention provides a method for preparing a small layer x% M using phosphate rock as raw material through microwave integration. a P b / BP device, comprising a microwave reactor, a gas membrane separator and a condensate collector; the microwave reactor comprises a feed port, an inert gas inlet, a slag outlet, a mixed gas outlet and an inert gas circulation inlet; the mixed gas outlet and the inert gas circulation inlet are both connected to the gas membrane separator; the gas membrane separator is connected to the condensate collector, and the condensate collector comprises a gaseous BP inlet, a gaseous x%M a P b / BP inlet and gaseous M a P b The gas membrane separator is connected to the gaseous BP inlet, gaseous x%M inlet and gaseous a P b / BP inlet and gaseous M a P b The inlet is connected; the gas membrane separator adopts an organic-inorganic hybrid composite membrane.
[0011] Preferably, the feed ports include a first feed port for adding screened phosphate ore, a second feed port for adding metal oxides, a third feed port for adding flux and non-metallic reducing agent, and a fourth feed port for adding a mixed catalyst.
[0012] Preferably, the device also includes a dust collector, a crusher and a photoelectric detector, and the discharge port of the photoelectric detector is connected to the first feeding port; the phosphate ore is removed by the dust collector, crushed by the crusher and screened by the photoelectric detector to obtain phosphate ore containing P2O5, SiO2, or containing P2O5, SiO2 and metal oxide components.
[0013] The present invention also provides a method for preparing a small layer of x% M by microwave integration using phosphate rock as raw material. a P b The method of / BP comprises the following steps:
[0014] Step (1), passing the mined phosphate ore through a dust collector to remove surface impurities; then passing the phosphate ore through a crusher to crush the phosphate ore; the phosphate ore is preferably crushed to a particle size of less than 3 mm;
[0015] Step (2), the crushed phosphate ore passes through a conveyor belt with a photoelectric detector, and the photoelectric detector is used to screen out the phosphate ore containing P2O5, SiO2, or containing P2O5, SiO2 and metal oxide components;
[0016] Step (3), under an inert gas environment, the screened phosphate ore is introduced into a microwave reactor through the first feeding port, and a non-metallic reducing agent and a flux are added through the third feeding port to carry out a redox reaction;
[0017] Step (4), increasing the microwave irradiation power, introducing the mixed catalyst into the microwave reactor through the fourth feed port; after the reaction is completed, the slag is discharged through the slag outlet, and the obtained mixed gas is introduced into the gas membrane separator, and the inert gas, waste gas and gaseous x%M are separated according to the selectivity of the membrane. a P b / BP separation, the separated inert gas enters the microwave reactor through the inert gas circulation inlet and is mixed with the inert gas entering the microwave reactor through the inert gas inlet for continued use; the gaseous x%M a P b / BP is passed into the condensation device for condensation and collection to obtain the lesser layer x%M a P b / BP.
[0018] Preferably, M is one or more of transition metals and metalloid elements, 0 < a ≤ 5, 0 < b ≤ 5, 0% ≤ x% ≤ 100%, where x% represents the mass percentage of M in the composite material, and a and b represent the molar ratio of metal element M to element P. a P b The mass percentage of, a and b represent the molar ratio of metal element M to element P.
[0019] Preferably, the M includes one or more of Fe, Mn, Mg, Ti, Ni, Co, Cu, Zn, Ru, Ga, In, Sr, Cr, As, Ge. By regulating the type and doping ratio of metal M, x% M a P b / BP composite materials with different excellent properties can be obtained.
[0020] Preferably, in step (3), other required metal oxides can also be added through the second feeding port in Figure 1 . The selected metal oxides in step (2) and the added other metal oxides in step (3) are selected from one or more of all transition metal oxides or metalloid oxides, preferably one or several of Fe2O3, MnO, MgO, TiO2, NiO, CoO, CuO, ZnO, RuO2, Ge2O3, In2O3, SrO, Cr2O3, As2O3, GeO2; the microwave irradiation power of the microwave reactor is 300 - 1500 W and is maintained for 30 - 90 min; the acidic flux or the acidic flux-containing agent is silica, forsterite, serpentine, etc.; the non-metal reducing agent is carbon (C).
[0021] Preferably, the total mass of the acidic flux or the acidic flux-containing agent is 15% - 30% of the raw material (mined phosphate rock); the mass of the non-metal reducing agent is 10% - 40% of the raw material (mined phosphate rock).
[0022] Preferably, in step (4), the microwave irradiation power is increased to 1600 - 3000 W and is maintained for 90 - 180 min.
[0023] The mixed gas is separated by a gas membrane separator to obtain inert gas, waste gas and gaseous x% M a P b / BP. The separated inert gas is returned to step (3) for reuse; the gas membrane separator uses an organic-inorganic hybrid composite membrane.
[0024] Preferably, in step (3), the flux is an acidic flux or contains an acidic flux, and the flux includes one or more of silica, forsterite, and serpentine; the total mass of the flux is 15%-30% of the raw materials, and the mass of the non-metallic reducing agent is 10%-40% of the raw materials; the raw materials are mined phosphate rock. The SiO2 contained in the phosphate rock can be used to replace part of the flux to achieve the full utilization of phosphate rock resources.
[0025] Preferably, in step (3), the non-metallic reducing agent is carbon; carbon has good microwave absorption ability, and under the action of microwave, point-to-point reduction can be achieved to efficiently obtain phosphorus单质 and metal phosphides.
[0026] Preferably, the inert gas is one or several of helium, neon, and argon.
[0027] Preferably, in step (4), the mixed catalyst is a mixture composed of a metal and iodine单质; the metal is one or several of metal单质 or alloys; the metal单质 is one or several of Sn, Bi, In, Pb, Cd; the alloy is one or several of AuSn, AgZn, PbSn, CdSn;
[0028] The mass ratio of the metal to iodine单质 in the mixed catalyst is (4-16):1; the mass ratio of the raw materials to the mixed catalyst is (5-10):1.
[0029] In the present invention, the mixed catalyst and microwave irradiation contribute to the formation of gaseous black phosphorus and metal phosphides, realizing instantaneous exfoliation, and finally rapid condensation can obtain x%M a P b / BP composite material, and the structure is uniform and the number of layers is small.
[0030] The present invention also provides a few-layer x%M a P b / BP, which is prepared by the above method; the x%M a P b / BP, that is, when x% = 0, it is BP; or, when 0% < x% < 100%, it is x%M a P b / BP; or, when x% = 100%, it is M a P b . The x%M a P b / BP has 2-10 layers. For example, in some embodiments, the few-layer x%M a P b / BP is x%FeCoMnP / BP, x%FeP / BP, x%GeP / BP, x%FeMnP / BP, x%Mn3P2, etc.
[0031] The present invention also provides a less-layer x%M a P b / BP application, the less layer x%M a P b / BP can be used in batteries, photoelectrocatalysis, energy storage, field effect transistors, sensors and other fields.
[0032] Compared with the prior art, the present invention has the following beneficial effects and advantages:
[0033] 1) Preparation of a few layers x% M by the microwave integration method of the present invention a P b / BP method, according to the different metal oxide contents in the raw materials, chooses to add or not add additional metal oxides, and separates different products such as few-layer black phosphorus, few-layer metal phosphide / black phosphorus composite materials or few-layer metal phosphides through gas separation membranes with different selectivities. The obtained products have excellent energy storage, photoelectrocatalytic and other properties, providing a new way for the large-scale preparation of such materials.
[0034] 2) The present invention realizes the integrated preparation of a small layer of x% M using phosphate rock as raw material a P b The device and process of / BP are easy to operate, with a wide source of raw materials and low prices. It makes full use of metal oxides, metal-like oxides and phosphorus in phosphate ore, saves mineral resources, and is more universal. It can be mass-produced and used in batteries, photoelectric catalysis, energy storage, field effect transistors, sensors and other fields.
[0035] 3) The present invention can utilize the metal oxides and metalloid oxides in the phosphate ore, and can also choose to add or not add additional metal oxides to achieve 0% M a P b / BP (i.e. BP), 0%<x%<100%M a P b / BP、100%M a P b / BP(i.e.M a P b ) Preparation of different forms of products, and microwave energy forces them to expand, obtaining a few layers x% M a P b / BP, which has excellent electrochemical and catalytic properties.
[0036] 4) The inert gas in the present invention can be recycled, which greatly reduces the cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The present invention uses phosphate rock as raw material to prepare a few layers of x% Ma P b / Schematic diagram of BP device;
[0038] Figure 2 is the XRD pattern of BP prepared in Example 1;
[0039] Figure 3 (a) and (b) are SEM images of BP prepared in Example 1, (c) is a SEM image of the FeP / BP composite material prepared in Example 2, and (d) is a TEM image of BP prepared in Example 1;
[0040] Figure 4 XRD pattern of FeP / BP prepared in Example 2;
[0041] Figure 5 XRD pattern of GeP / BP prepared in Example 3;
[0042] Figure 6 XRD pattern of FeMnP / BP prepared in Example 4;
[0043] Figure 7 XRD pattern of FeCoMnP / BP prepared in Example 5;
[0044] Figure 8 This is a photodegradation performance evaluation diagram based on the GeP / BP composite catalyst in Example 3;
[0045] Fig. 9 This is a photodegradation performance evaluation diagram based on the FeMnP / BP composite catalyst in Example 4;
[0046] Fig.10 This is a graph for evaluating the photocatalytic hydrogen production performance based on the FeCoMn / BP composite catalyst in Example 5;
[0047] Fig.11 This is a graph evaluating the photocatalytic hydrogen production performance based on Mn3P2 catalyst in Example 6.
[0048] Reference numerals:
[0049] A-second feed port; B-third feed port; C-fourth feed port; D-inert gas inlet; E-waste residue outlet; F-mixed gas outlet; G-inert gas circulation inlet; H-first feed port; I-waste gas outlet; J-gaseous M a P b Inlet; K-gaseous x%M a P b / BP inlet; L-gaseous BP inlet. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are preferred embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Figure 1 The invention discloses a method for preparing a small layer of x% M by microwave integration using phosphate rock as raw material. a P b Schematic diagram of a device of / BP, the device comprising a microwave reactor, a gas membrane separator and a condensate collector; the microwave reactor comprises a feed port, an inert gas inlet D, a waste residue outlet E, a mixed gas outlet F and an inert gas circulation inlet G; the mixed gas outlet F and the inert gas circulation inlet G are both connected to the gas membrane separator; the gas membrane separator is connected to the condensate collector, and the gas membrane separator adopts an organic-inorganic hybrid composite membrane; the gas membrane separator is provided with a waste gas outlet I, and the condensate collector comprises a gaseous M a P b Inlet J, gaseous x%M a P b / BP inlet K and gaseous BP inlet L, the gas membrane separator is connected to the gaseous BP inlet L, gaseous x%M of the condensation collector through three pipelines. a P b / BP inlet K and gaseous M a P b The inert gas inlet D is connected to an external inert gas tank.
[0052] The feed ports include a first feed port H for adding screened phosphate ore, a second feed port A for adding metal oxides, a third feed port B for adding flux and non-metallic reducing agent, and a fourth feed port C for adding a mixed catalyst.
[0053] The device also includes a dust collector, a crusher and a photoelectric detector, and the discharge port of the photoelectric detector is connected to the first feeding port of the microwave reactor; the phosphate ore is removed by the dust collector, crushed by the crusher and screened by the photoelectric detector to obtain phosphate ore containing P2O5, SiO2, or containing P2O5, SiO2 and metal oxide components, and the screened phosphate ore directly enters the microwave reactor through the first feeding port. In this way, a device integrating phosphate ore raw material screening, microwave reaction and product separation is obtained, which can realize the efficient utilization of phosphate ore and obtain value-added products with excellent performance, and has broad prospects for industrial application.
[0054] The present invention provides a method for preparing a small layer of x% M by microwave integration using phosphate rock as raw material. a P b / BP method, the method comprising the following steps:
[0055] (1) passing the mined phosphate ore through a dust collector to remove surface impurities; then passing the phosphate ore through a crusher to crush the phosphate ore; the phosphate ore is crushed to a particle size of less than 3 mm;
[0056] (2) The crushed phosphate ore passes through a conveyor belt with a photoelectric detector, and the photoelectric detector is used to screen out the phosphate ore containing P2O5, SiO2, or P2O5, SiO2 and metal oxide components;
[0057] (3) Under an inert gas environment, the screened phosphate ore is introduced into a microwave reactor, and a non-metallic reducing agent and a flux (acidic flux or containing an acidic flux) are added through a third feed port B to carry out a redox reaction.
[0058] If necessary, you can also Figure 1 The second feeding port A in the reactor is used to add other metal oxides as needed. The selected metal oxides and the added other metal oxides can be all transition metal oxides or metalloid oxides, preferably one or more of Fe2O3, MnO, MgO, TiO2, NiO, CoO, CuO, ZnO, RuO2, Ge2O3, In2O3, SrO, Cr2O3, As2O3, and GeO2. Specifically, the microwave irradiation power of the microwave reactor is 300-1500W, and the oxidation-reduction reaction is maintained for 30-90 minutes; the acidic flux or the acidic flux is silicon dioxide, forsterite, serpentine, etc.; the non-metallic reducing agent is carbon (C, and the C used in the following embodiments is coke);
[0059] The total mass of the acid flux or the acid flux-containing agent is 15%-30% of the raw material (mined phosphate ore); the mass of the non-metallic reducing agent is 10%-40% of the raw material (mined phosphate ore);
[0060] (4) Continue to increase the microwave irradiation power to 1600-3000W, and introduce the mixed catalyst into the microwave reactor through the fourth feed port C, and keep it for 90-180 minutes; after the reaction is completed, the slag is discharged through the waste slag outlet E, and the obtained mixed gas is introduced into the gas membrane separator, and the inert gas, waste gas and gaseous x%M are separated according to the selectivity of the membrane. a P b / BP separation, the separated inert gas enters the microwave reactor through the inert gas circulation inlet G and is mixed with the inert gas entering the microwave reactor through the inert gas inlet D for continued use; the gaseous x%M a P bThe less-layered x%M a P b / BP can be obtained by condensing and collecting it through a condensation device with BP introduced
[0061] The mixed catalyst is a mixture of one or more of metal单质, alloy and iodine; the metal单质 is one or more of Sn, Bi, In, Pb, Cd, and the alloy is one or more of AuSn, AgZn, PbSn, CdSn. The mass ratio of the metal单质 and / or alloy to iodine in the mixed catalyst is (4-16):1; the mass ratio of the raw material (mined phosphate rock) to the mixed catalyst is (5-10):1
[0062] The method of the present invention can realize continuous preparation of less-layered x%M a P b / BP, and according to the different raw materials entering the microwave reactor, black phosphorus (BP), a composite material of metal phosphide and black phosphorus (x%M a P b / BP), and metal phosphide (M a P b ) can be obtained respectively; wherein, M is one or more of transition metal and metalloid elements, 0 < a ≤ 5, 0 < b ≤ 5, 0% ≤ x% ≤ 100%, and x% represents the mass percentage of M a P b in the composite material. This method does not limit the grade of phosphate rock, makes full use of metal oxides, metalloid oxides and phosphorus elements in phosphate rock, has a simple and easy operation process, greatly reduces production costs, and is conducive to integrated large-scale production
[0063] The present invention will be elaborated in detail through specific embodiments below
[0064] Table 1 Sources and main component compositions of phosphate rock in each embodiment of the present invention
[0065]
[0066]
[0067] Example 1 Preparation of less-layered BP and application of the prepared BP in the negative electrode of lithium-ion battery
[0068] A method for microwave integration preparation of less-layered BP with phosphate rock as raw material, comprising the following steps
[0069] (1) As shown Figure 1 , 1000 g of phosphate rock is removed of surface impurities through a dust remover; then the phosphate rock is crushed to a particle size of less than 3 mm through a crusher
[0070] (2) The crushed phosphate rock is screened out by a photoelectric detector to obtain phosphate rock containing P2O5 and SiO2;
[0071] (3) The screened phosphate rock was introduced into a microwave reactor, 100 g of silicon dioxide and 100 g of reducing agent C were added through port B, and the microwave irradiation power was 600 W for 30 min to carry out redox reaction;
[0072] (4) Continue to increase the microwave irradiation power to 1600W, and introduce 80g Sn and 20g I2 mixed catalyst into the microwave reactor through the C port, and keep it for 100min to obtain a mixed gas; the obtained mixed gas is introduced into a gas membrane separator (all embodiments use the following gas separation membrane: (1) 2mL of tetraethyl orthosilicate, 2mmol of pyromellitic anhydride and 2mmol of 4,4-diaminodiphenyl ether are added to 10mL of N,N-dimethylformamide, 10mL of dichloromethane and 20mL of anhydrous ethanol mixed solvent, and reacted in a constant temperature oil bath at 60°C for 12 hours to form a molding liquid, which is spin-coated on a glass plate and vacuum-dried at 60°C for 24 hours to obtain a membrane for separating inert gases. (2) 2mL of tetraethyl orthosilicate, 2mmol of pyromellitic anhydride and 2mmol of 4,4-diaminodiphenyl ether are added to 15mL of The mixture was added with N,N-dimethylformamide, 15 mL of dichloromethane and 30 mL of anhydrous ethanol as a mixed solvent, and reacted in a constant temperature oil bath at 60° C. for 12 hours. Then, 2 mmol of ligand 2-aminoterephthalic acid (or 2 mmol of 1,2,4,5-benzenetetramine and 1 mL of tetrabutyl titanate, or 2 mmol of 2-aminobenzimidazole) was added, and reacted in a constant temperature oil bath at 80° C. for 12 hours to form a molding liquid, which was spin-coated on a glass plate and vacuum-dried at 60° C. for 24 hours to obtain the product BP (or x% M of Example 2-5) for separation. a P b / BP, or M of Example 6 a P b ) membrane. According to the selectivity of the membrane, the inert gas, waste gas and gaseous BP are separated (the inert gas and gaseous BP selectively permeate the membrane for separating the inert gas and the membrane for separating the product BP, respectively, and the remaining waste gas is output from the waste gas outlet). The inert gas obtained after separation is mixed with the newly input inert gas and enters the microwave reactor for continued use; the gaseous BP is condensed to obtain a solid of 126.21 g, with a yield of 95.4%, which is recorded as sample 1.
[0073] The yield is calculated as follows: the P2O5 content in the phosphate rock is 303 g, which is converted into a phosphorus content of 132.30 g. Finally, 126.21 g of product is obtained by condensation. The actual mass of the product is 95.4% higher than the theoretical mass.
[0074] like Figure 2As shown, it can be seen that in the XRD of BP, except for the characteristic diffraction peak of black phosphorus (BP), there are no other impurity peaks, which proves that BP is successfully prepared.
[0075] like Figure 3 As shown, from Figure 3 As can be seen in (a), the prepared black phosphorus is a sheet-like structure. Figure 3 In (b) and (d), it can be seen that the prepared black phosphorus (BP) is a few-layer sheet structure, in which Figure 3 In (b), it can be seen that the prepared black phosphorus (BP) is approximately 2 layers.
[0076] The electrochemical properties of the obtained samples were measured by the following method: the negative electrode film was made of sample 1 obtained in Example 1, acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 80:5:15, with a thickness of about 0.1 mm, and the negative electrode film was rolled onto a stainless steel mesh to form a negative electrode sheet; a metal lithium sheet was used as the positive electrode, the separator was a polypropylene microporous membrane, the electrolyte was a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) containing 1.5 mol / L LiPF6, wherein the volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC) was 1:1, and a CR2032 button cell was assembled under vacuum conditions, and a charge and discharge test was carried out at room temperature, with a charge and discharge range of 2.5-4.2 V. Its first charge capacity was 1990 mAh / g, and after 100 charge and discharge cycle experiments, the charge capacity was 1791 mAh / g, and the capacity retention rate was 90%, with high capacity and excellent cycle performance.
[0077] Example 2: Preparation of few-layer FeP / BP and application of the prepared FeP / BP composite material in the negative electrode of lithium-ion battery
[0078] A method for preparing a few layers of x% FeP / BP by microwave integration using phosphate rock as a raw material comprises the following steps:
[0079] (1) 1000 g of phosphate rock is passed through a dust collector to remove surface impurities; the phosphate rock is then crushed into a particle size of less than 3 mm by a crusher;
[0080] (2) The crushed phosphate rock is screened out by a photoelectric detector to obtain phosphate rock containing P2O5, SiO2 and Fe2O3;
[0081] (3) The screened phosphate rock was introduced into a microwave reactor, 80 g of silicon dioxide and 120 g of C were added through port B, the microwave irradiation power was 800 W, and the reaction was maintained for 40 min to carry out redox reaction;
[0082] (4) The microwave irradiation power was further increased to 1600 W, and 90 g of Bi and 10 g of I2 mixed catalyst were introduced into the microwave reactor through the C port and maintained for 120 min. The obtained mixed gas was introduced into a gas membrane separator, and the inert gas, waste gas and gaseous 18.13% FeP / BP were separated according to the selectivity of the membrane (the inert gas selectively permeated the membrane used to separate the inert gas, and the gaseous FeP / BP selectively permeated the membrane used to separate the product FeP / BP. The remaining waste gas was output from the waste gas outlet. The separation principle of the following embodiments is the same and will not be repeated here). The inert gas obtained after separation was mixed with the newly input inert gas and continued to be used; the gaseous 18.13% FeP / BP was condensed to obtain a few-layer FeP / BP solid of 134.99 g with a yield of 96%, which was recorded as sample 2.
[0083] The yield calculation method is: first calculate the Fe content of 15.75g through Fe2O3, then calculate the FeP mass of 24.27g based on the Fe content, and the FeP mass accounts for 134.99 of the total mass, so the FeP content in the final product is 18.13%. According to the complete reaction of the screened Fe and P, the final product should be 140.6g in theory. Therefore, the ratio of the actual mass of the final product to the mass of the theoretical final product is a yield of 96%. The calculation method of the following embodiments is the same and will not be repeated.
[0084] like Figure 4 As shown, it can be seen that in the XRD of FeP / BP, in addition to the characteristic diffraction peak of black phosphorus (BP), the (211) crystal plane of FeP also appears, proving that the FeP / BP composite material is successfully prepared.
[0085] like Figure 3 As shown, from Figure 3 As can be seen in (c), the prepared FeP / BP composite material is a lamellar structure with approximately 3-4 layers.
[0086] The electrochemical properties of the obtained samples were measured by the following method: the negative electrode film was made of sample 2 obtained in Example 2, acetylene black and PVDF in a mass ratio of 80:5:15, with a thickness of about 0.1 mm, and the negative electrode film was rolled onto a stainless steel mesh to form a negative electrode sheet; a metal lithium sheet was used as the positive electrode, the separator was a polypropylene microporous membrane, the electrolyte was a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) containing 1.5 mol / L LiPF6, wherein the volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC) was 1:1, and a CR2032 button cell was assembled under vacuum conditions, and a charge and discharge test was carried out at room temperature, with a charge and discharge range of 2.5-4.2 V. Its first charge capacity was 2253 mAh / g, and after 100 charge and discharge cycle experiments, the charge capacity was 2073 mAh / g, and the capacity retention rate was 92%, with high capacity and excellent cycle performance.
[0087] Example 3: Preparation of few-layer GeP / BP and evaluation of photodegradation performance of the prepared GeP / BP as a composite catalyst
[0088] A method for preparing a few layers of x% GeP / BP by microwave integration using phosphate rock as a raw material comprises the following steps:
[0089] (1) 1000 g of phosphate rock is passed through a dust collector to remove surface impurities; the phosphate rock is then crushed into a particle size of less than 3 mm by a crusher;
[0090] (2) The crushed phosphate rock is screened out by a photoelectric detector to obtain phosphate rock containing P2O5, SiO2 and GeO2;
[0091] (3) The screened phosphate rock is introduced into a microwave reactor, and GeO2 with a mass of 0% of the raw material (phosphate rock) is added through port A, and 150 g of forsterite and 200 g of C are added through port B. The microwave irradiation power is 700 W and maintained for 45 min to carry out redox reaction;
[0092] (4) The microwave irradiation power was further increased to 2000 W, and 160 g of Pb and 40 g of I2 mixed catalyst were introduced into the microwave reactor through the C port and maintained for 120 min. The obtained mixed gas was introduced into a gas membrane separator, and the inert gas, waste gas and gaseous 13.94% GeP / BP were separated according to the selectivity of the membrane. The inert gas obtained after separation was mixed with the newly input inert gas for continuous use; the gaseous 13.94% GeP / BP was condensed to obtain a total of 146.37 g of solid with a yield of 94.5%, which was recorded as sample 3-a.
[0093] The above process was repeated, except that the mass of GeO2 added in step (3) was 1.5% or 3% of the raw material, and the other conditions and steps were the same. When the mass of GeO2 added was 1.5% of the raw material, the gaseous 22.41% GeP / BP obtained by membrane separation in step (4) was condensed to obtain a solid of 157.37 g, with a yield of 95.2%, which was recorded as sample 3-b. When the mass of GeO2 added was 3% of the raw material, the gaseous 30.48% GeP / BP obtained by membrane separation in step (4) was condensed to obtain a solid of 164.46 g, with a yield of 93.6%, which was recorded as sample 3-c.
[0094] like Figure 5 As shown, it can be seen that in the XRD of GeP / BP, in addition to the characteristic diffraction peak of black phosphorus (BP), the (220) crystal plane of GeP also appears, proving that the GeP / BP composite material is successfully prepared.
[0095] 50 mg of samples 3-a, 3-b, and 3-c were taken as catalysts, and a xenon lamp (350 W) was used as a light source to simulate sunlight to degrade RhB (rhodamine B, the concentration of which was 1×10 -4 mol / L). Degradation process: first dark adsorption for 30 minutes, then turn on the xenon lamp and take samples every 10 minutes, separate the liquid by centrifuge, and measure it by UV-visible spectrophotometer to know the degree of degradation, such as Figure 8 As shown, sample 3-b was selected as the catalyst, and the degradation rate of RhB reached 99.8% after 60 minutes of illumination.
[0096] Example 4. Preparation of few-layer FeMnP / BP and evaluation of the photocatalytic hydrogen production performance of the prepared FeMnP / BP as a composite catalyst
[0097] A method for preparing a few layers of x% FeMnP / BP by microwave integration using phosphate rock as a raw material comprises the following steps:
[0098] (1) 1000 g of phosphate rock is passed through a dust collector to remove surface impurities; the phosphate rock is then crushed into a particle size of less than 3 mm by a crusher;
[0099] (2) The crushed phosphate rock is screened out by a photoelectric detector to obtain phosphate rock containing P2O5, SiO2, Fe2O3 and MnO;
[0100] (3) The screened phosphate rock is introduced into a microwave reactor, and 0.5% (or 1.5%, or 2%) of MnO by weight of the raw material is added through port A, and 280g of silicon dioxide and 200g of C are added through port B. The microwave irradiation power is 800W and maintained for 60 minutes to carry out redox reaction;
[0101] (4) The microwave irradiation power was further increased to 1800 W, and 120 g of AgZn and 30 g of I2 mixed catalyst were introduced into the microwave reactor through port C and maintained for 150 min. The obtained mixed gas was introduced into a gas membrane separator, and the inert gas, waste gas and gaseous 26.28% FeMnP / BP (when 1.5% MnO was added, 30.95% FeMnP / BP was obtained; when 2% MnO was added, 33.53% FeMnP / BP was obtained) were separated according to the selectivity of the membrane. The separated inert gas was mixed with the inert gas inputted from the inert gas inlet and used continuously. The gaseous 26.28% FeMnP / BP (when 1.5% MnO was added, 30.95% FeMnP / BP was obtained; when 2% MnO was added, 33.53% FeMnP / BP was obtained) were separated from each other according to the selectivity of the membrane. FeMnP / BP) was condensed by a condensation collector to obtain a total of 144.31 g of solid (154.51 g when 1.5% MnO was added; 157.40 g when 2% MnO was added), with a yield of 94.2% (96.0% when 1.5% MnO was added; 95.5% when 2% MnO was added), recorded as sample 4-a (4-b when 1.5% MnO was added; 4-c when 2% MnO was added).
[0102] like Figure 6 As shown, it can be seen that in the XRD of FeMnP / BP, in addition to the characteristic diffraction peaks of black phosphorus (BP), the (002) and (211) crystal planes of FeMnP also appear, proving that the FeMnP / BP composite material is successfully prepared.
[0103] 50 mg of samples 4-a, 4-b, and 4-c were taken as catalysts, and a xenon lamp (350 W) was used as a light source to simulate sunlight to degrade reactive red X-3B dye (the concentration of each sample was 1×10 -4 mol / L). Degradation process: first dark adsorption for 30 minutes, then turn on the xenon lamp to take samples every 5 minutes, separate the liquid by centrifuge, and measure it by UV-visible spectrophotometer to know the degree of degradation, such as Fig. 9 As shown, sample 4-b was selected as the catalyst, and the degradation rate of reactive red X-3B dye reached 99.9% after 30 minutes of light exposure.
[0104] Example 5. Preparation of few-layer FeCoMnP / BP and evaluation of the photodegradation performance of the prepared FeCoMnP / BP as a composite catalyst
[0105] A method for preparing a few layers of x% FeCoMnP / BP by microwave integration using phosphate rock as a raw material comprises the following steps:
[0106] (1) 1000 g of phosphate rock is passed through a dust collector to remove surface impurities; the phosphate rock is then crushed into a particle size of less than 3 mm by a crusher;
[0107] (2) The crushed phosphate rock is screened out by a photoelectric detector to obtain phosphate rock containing P2O5, SiO2, Fe2O3 and MnO;
[0108] (3) The screened phosphate rock is introduced into a microwave reactor, and CoO with a mass of 1% (or 2%, or 3%) of the raw material is added through port A, and 300g of forsterite and 200g of C are added through port B. The microwave irradiation power is 800W and maintained for 50 minutes to carry out redox reaction;
[0109] (4) The microwave irradiation power was further increased to 1700 W, and 180 g of Sn and 20 g of I2 mixed catalyst were introduced into the microwave reactor 2 through the C port, and the mixture was kept for 150 min. The obtained mixed gas was introduced into the gas membrane separator, and the inert gas, the waste gas and the gaseous 25.95% FeCoMnP / BP (when 2% CoO was added, 29.74% FeCoMnP / BP was obtained; when 3% CoO was added, 35.48% FeCoMnP / BP was obtained) were separated according to the selectivity of the membrane. The inert gas obtained after separation was mixed with the newly input inert gas for continuous use; the gaseous 25.95% FeCoMnP / BP (when 2% CoO was added, 29.74% FeCoMnP / BP was obtained; when 3% CoO was added, 35.48% FeCoMnP / BP was obtained) were separated. FeCoMnP / BP) was condensed to obtain a total of 161.13 g of solid (173.17 g when 2% CoO was added; 177.87 g when 3% CoO was added), with a yield of 93.2% (95.8% when 2% CoO was added; 94.3% when 3% CoO was added), recorded as sample 5-a (5-b when 2% CoO was added; 5-c when 3% CoO was added).
[0110] like Figure 7 As shown, it can be seen that in the XRD of FeCoMnP / BP, in addition to the characteristic diffraction peaks of black phosphorus (BP), the (002), (200) and (211) crystal planes of FeCoMnP also appear, proving that the FeCoMnP / BP composite material is successfully prepared.
[0111] 50 mg of samples 5-a, 5-b, and 5-c were taken as catalysts, and the test of photocatalytic decomposition of water to generate H2 gas was carried out using an all-glass automatic online trace gas analysis system (Labsolar 6A). 50 mg of catalyst was added to 100 mL of methanol / H2O solution (volume ratio 1:4), and a 300W xenon lamp was used as a light source to simulate sunlight. Before the reaction, the reaction solution was bubbled with high-purity argon for 30 minutes, and magnetic stirring was performed during the reaction. The generated gas was analyzed using a gas chromatograph (GC9790plus), as shown in FIG. Fig.10As shown, the hydrogen production of sample 5-b as a catalyst is 33.8 mmol / g.
[0112] Example 6 Preparation of few-layer Mn3P2 and evaluation of the photocatalytic hydrogen production performance of the prepared Mn3P2 as a catalyst
[0113] (1) 1000 g of phosphate rock is passed through a dust collector to remove surface impurities; the phosphate rock is then crushed into a particle size of less than 3 mm by a crusher;
[0114] (2) The crushed phosphate rock is screened out by a photoelectric detector to obtain phosphate rock containing P2O5, SiO2 and MnO;
[0115] (3) The screened phosphate rock was introduced into a microwave reactor, 37.91% MnO by weight of the raw material was added through port A, 200 g serpentine and 120 g C were added through port B, and the microwave irradiation power was 900 W for 80 min to carry out redox reaction;
[0116] (4) The microwave irradiation power was further increased to 1900 W, and 130 g of AuSn and 20 g of I2 mixed catalyst were introduced into the microwave reactor through the C port and maintained for 180 min. The obtained mixed gas was introduced into a gas membrane separator, and the inert gas, waste gas and gaseous Mn3P2 were separated according to the selectivity of the membrane. The inert gas was mixed with the original inert gas and continued to be used; the gaseous Mn3P2 was condensed to obtain a total of 424.50 g of solid with a yield of 98.95%, which was recorded as Sample 6.
[0117] 50 mg of Mn3P2, MnO, and P2O5 were taken as catalysts respectively, and the experiment of photocatalytic decomposition of water to generate H2 gas was carried out using an all-glass automatic online trace gas analysis system (Labsolar 6A). 50 mg of catalyst was added to 100 mL of methanol / H2O solution (volume ratio 1:4), and a 300W xenon lamp was used as the light source to simulate sunlight. Before the reaction, the reaction solution was bubbled with high-purity argon for 30 minutes, and magnetic stirring was performed during the reaction. The generated gas was analyzed using a gas chromatograph (GC9790plus), as shown in FIG. Fig.11 As shown, the hydrogen production capacity of the prepared Mn3P2 as a catalyst is 36.5 mmol / g.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A microwave-integrated method for preparing a few layers of x% M using phosphate rock as raw material a P b / BP method, characterized in that The following steps are involved: Step (1), the mined phosphate ore is passed through a dust collector to remove surface impurities, and then the phosphate ore is crushed into a particle size of less than 3 mm by a crusher; Step (2), the crushed phosphate ore passes through a conveyor belt with a photoelectric detector, and the photoelectric detector is used to screen out the phosphate ore containing P2O5, SiO2, or containing P2O5, SiO2 and metal oxide components; Step (3), under an inert gas environment, the phosphate ore screened in step (2) is introduced into a microwave reactor through the first feeding port, and a non-metallic reducing agent and a flux are added through the third feeding port to carry out a redox reaction; Step (4), increasing the microwave irradiation power, introducing the mixed catalyst into the microwave reactor through the fourth feed port; after the reaction is completed, the slag is discharged through the slag outlet, and the obtained mixed gas is introduced into the gas membrane separator, and the inert gas, waste gas and gaseous x%M in the mixed gas are separated according to the selectivity of the membrane. a P b / BP separation; gaseous x%M a P b / BP is passed into the condensation device for condensation and collection to obtain the lesser layer x%M a P b / BP; Wherein, BP represents black phosphorus, the non-metallic reducing agent is carbon, the mixed catalyst is a mixture of metal and iodine, the metal is one or more of metal single substance or alloy; the metal single substance is one or more of Sn, Bi, In, Pb, Cd; the alloy is one or more of AuSn, AgZn, PbSn, CdSn; 0 < a ≤ 5, 0 < b ≤ 5, 0% ≤ x% ≤ 100%, where x% represents the mass percentage of M in the resulting product, and a and b represent the molar ratio of metal element m and element p; a P b in the product, a and b represent the molar ratio of metal element m and element p; The M is one or more of Fe, Mn, Mg, Ti, Ni, Co, Cu, Zn, Ru, Ga, In, Sr, Cr, As, and Ge. By adjusting the type and doping ratio of the metal M, x% M with different excellent properties can be obtained. a P b / BP.
2. The method according to claim 1, characterized in that The step (3) further comprises adding other metal oxides as required through the second feeding port as needed; the screened metal oxides and the added other metal oxides are selected from one or more of all transition metal oxides or metalloid oxides.
3. The method according to claim 2, characterized in that The screened metal oxides and other added metal oxides include one or more of Fe2O3, MnO, MgO, TiO2, NiO, CoO, CuO, ZnO, RuO2, Ge2O3, In2O3, SrO, Cr2O3, As2O3, and GeO2.
4. The method according to claim 1, characterized in that: In the step (3), the microwave irradiation power of the microwave reactor is 300-1500 W and maintained for 30-90 minutes.
5. The method according to claim 1, characterized in that The flux is an acid flux or an acid-containing flux, and the mass of the acid flux or the acid-containing flux is 15%-30% of the mass of the phosphate ore mined in the step (1); its mass is 10%-40% of the mass of the phosphate ore mined in the step (1).
6. The method according to claim 5, characterized in that The flux is one or more of silicon dioxide, forsterite and serpentine.
7. The method according to claim 1, characterized in that In the step (4), increasing the microwave irradiation power means increasing the microwave irradiation power to 1600-3000W and maintaining it for 90-180min; The mixed gas is separated into inert gas, waste gas and gaseous x%M by a gas membrane separator. a P b / BP, the separated inert gas is returned to step (3) for reuse.
8. The method according to claim 1, characterized in that: The inert gas is one or more of helium, neon and argon.
9. The method according to claim 1, characterized in that: In the step (4), the mass ratio of the metal to the iodine element in the mixed catalyst is (4-16):1; and the mass ratio of the mined phosphate ore to the mixed catalyst in the step (1) is (5-10):
1.
10. A microwave-integrated method for preparing a few layers of x% M using phosphate rock as raw material a P b / BP device, characterized in that The invention comprises a microwave reactor, a gas membrane separator and a condensate collector; the method according to any one of claims 1 to 9 is implemented in the device, the microwave reactor comprises a feed port, an inert gas inlet, a slag outlet, a mixed gas outlet and an inert gas circulation inlet; the mixed gas outlet and the inert gas circulation inlet are both connected to the gas membrane separator; the gas membrane separator is connected to the condensate collector, and the condensate collector comprises a gaseous BP inlet, a gaseous x%M a P b / BP inlet and gaseous M a P b inlet; the gas membrane separator adopts an organic-inorganic hybrid composite membrane; the feed port includes a first feed port for adding the screened phosphate ore, a second feed port for adding metal oxides, a third feed port for adding flux and non-metallic reducing agent, and a fourth feed port for adding a mixed catalyst; the phosphate ore is removed by a dust collector, crushed by a crusher, and screened by a photoelectric detector to obtain phosphate ore containing P2O5, SiO2, or containing P2O5, SiO2 and metal oxide components.
11. Application of the product obtained by the method according to any one of claims 1 to 9 in the fields of batteries, photoelectrocatalysis, energy storage, field effect transistors or sensors.
Citation Information
Patent Citations
Preparation method of nickel phosphide nanosheet and nickel phosphide nanosheet prepared by method thereof
CN112607716A
Continuous preparation method of black phosphorus
CN108128761A
A transition metal phosphide MxPy oxygen reduction and hydrogen evolution bifunctional catalyst and preparation method and application thereof
CN109119647A